THE ROLE OF PERFORMANCE ON THE RELATIONSHIP FACTORS AFFECTING FIRM VALUE - Nabila, Riezka Laila; Safiq, Muhamad (Soedirman Accounting, Auditing and Public Sector Journal, 2025)
This research aims to examine the effect of green accounting, Corporate Social Responsibility, institutional ownership, board size on firm value with the moderating role of company performance proxied by profitability. This research is quantitative research. Data collection was carried out using secondary data obtained through annual reports listed on the Indonesia Stock Exchange. This study used 46 manufacturing companies from the period 2017-2021. Sampling was carried out using purposive sampling method. The results of this study found that green accounting, institutional ownership, board size have no significant effect on firm value. However, only Corporate Social Responsibility has a significant effect on firm value. Furthermore, performance strengthens the relationship between green accounting and firm value. Performance strengthens the relationship between CSR and firm value. Meanwhile, performance weakens the relationship between institutional ownership and firm value. Performance weakens the relationship between board size and firm value.